FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS MIKROBIOLOGIS JAJANAN BATAGOR DI KECAMATAN TEMBALANG - Suci Amalia Febriyanti; Retno Hestiningsih; Praba Ginandjar; M. Arie Wuryanto (Jurnal Kesehatan Masyarakat (Undip), 2019)
Batagor is a category of processed food made from fish or meat which if food processing is not hygiene sanitanitation. The contamination of batagor can be caused by the principle of food sanitation hygiene that is not implemented properly. The purpose of this study was to analyze the relationship between traders' sanitation hygiene with microbiological quality on batagor snacks in Tembalang District. This research was observational analytic with cross sectional study. The study population was all batagor sellers in Tembalang District. The sample technique used saturated sampling techniques as many as 31 traders. Interviews and observations were made on hygiene practices, health conditions, location safety, water sanitation, quality of raw materials, and practice of storing raw materials. Data analysis used fisher exact test. The results obtained 80.6% of the samples had MPN values exceeding the limit, 48.4% were contaminated with Escherichia coli, and 29% of the samples were overgrown with fungi. 80.6% of the samples did not meet food microbiological requirements. The analysis showed that microbiologic quality associated with hygiene practices (p = 0.028), place sanitation (p = 0.021), and water sanitation (p = 0.018) in batagor traders with microbiological quality. It can be assumed that there is a correlation between hygiene practices, place sanitation, and water sanitation with the microbiological quality of batagor. Related institutions are expected to be able to improve supervision and management of street vendors to meet the stipulated health requirements.